2022
DOI: 10.1021/acs.jpcc.2c03847
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Intersystem Crossing in Selenium-Annulated Perylene Bisimide

Abstract: An intersystem crossing (ISC), the non-radiative transition between two electronic states with different spin multiplicities, is ubiquitous and imperative in molecular photochemistry. The manifestation of a triplet manifold in π-conjugated chromophoric materials has a crucial role in enhancing the efficiency of photofunctional devices. Herein, we explore the triplet-state population in a series of chalcogen-annulated perylene bisimides (O-PBI, S-PBI, and Se-PBI), where the selenium-annulated PBI (Se-PBI) exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…This more important quenching of the fluorescence suggests the possibility of an intersystem crossing induced by the introduction of heavy atoms, already reported for S and Se functionalized PDIs. 40 CV was then performed in dichloromethane with 0.1 M n -Bu 4 NPF 6 as a supporting electrolyte and the Fc + /Fc couple as a reference to determine the electronic properties of these dyes (Fig. S5, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…This more important quenching of the fluorescence suggests the possibility of an intersystem crossing induced by the introduction of heavy atoms, already reported for S and Se functionalized PDIs. 40 CV was then performed in dichloromethane with 0.1 M n -Bu 4 NPF 6 as a supporting electrolyte and the Fc + /Fc couple as a reference to determine the electronic properties of these dyes (Fig. S5, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…Although this approach can potentially enhance ISC, our previous investigations showed that the selective acceleration of rISC can be achieved by a controlled incorporation of bromine atoms into the structure of TADF emitters . Analysis of the literature also evidenced that the various modifications of TADF emitters with HAs can significantly improve their photophysical kinetic properties. …”
Section: Introductionmentioning
confidence: 99%
“…In our lab, we use a wide range of techniques from organic synthesis, crystal engineering, spectroscopy and computational chemistry to identify distinct chromophoric systems and architectures exhibiting exciting and emergent photophysical properties. [4][5][6][7][8][9][10] In this article, we will focus on a particular intermolecular packing feature-the interchromophoric twist, whose photophysical relevance and importance we are still exploring, and in course, will also touch upon the recent experimental and theoretical reports we have communicated along this line. We first elaborate on the importance of the rotation angle as a tool to fine-tune the interchromophoric interactions and serve as a potentially new design guideline for efficient singlet fission (SF), a current, hot topic of research to better harness solar energy through photon energy conversion.…”
Section: Introductionmentioning
confidence: 99%